Effort–reward imbalance as a risk factor for disability pension: the Finnish Public Sector Study - Anne Juvani; Tuula Oksanen; Paula Salo; Marianna Virtanen; Mika Kivimäki; Jaana Pentti; Jussi Vahtera (Scandinavian Journal of Work, Environment & Health, 2014)

(untitled)
OBJECTIVES: Job strain has previously been shown to predict disability pension, but it is unknown whether effort-reward imbalance (ERI), another major stress model, is also associated with disability pension. METHODS: We examined ERI as a risk factor for diagnosis-specific disability pension in a cohort of 51 874 public-sector employees in Finland. To control for reporting bias, work unit-level scores of ERI (based on the survey responses of 35 260 employees in 2000–2002) were constructed and linked to all eligible employees. A sub-cohort of the respondents was analyzed also with individual-level ERI. Disability pension data were derived from national pension registers with no loss to follow-up. The outcomes were all-cause disability pension and disability pension due to depression, musculoskeletal diseases, and ischemic heart diseases (IHD). Multivariate Cox proportional hazard models (adjusted for sociodemographic factors, baseline health, and work-related characteristics) were used for analyses. RESULTS: During a mean 8.9 years of follow-up, 4542 participants were granted disability pension. An increased risk for disability pension due to depression was detected for both high work unit- and individual-level ERI [hazard ratio (HR) 1.63, 95% confidence interval (95% CI) 1.31–2.04 and HR 1.90, 95% CI 1.51–2.40, respectively]. High individual-level ERI increased the risk of disability pension due to musculoskeletal diseases (HR 1.32, 95% CI 1.13–1.53), but no association was observed for work unit-level ERI (HR 1.02, 95% CI 0.88–1.19). ERI was not associated with disability pension due to IHD. CONCLUSION: The present study showed a consistent association between high ERI and an increased risk of disability pension due to depression.